You want this goonvernment ah? - Kee, Thuan Chye (Gerakbudaya Enterprise, 2018)
Wah! Najib said RM500 could feed a whole family for a year!He bought a chicken for RM1 and told us to shop wisely!Umno MP said M01 was the Agong! ROTF!Alamak! So many scandals at Felda!Ahmad Maslan said with GST, some good cheaper wor!Menteri Besar challenged Opposition man to a fight!Celaka! Najib broke his promise to repeal the Sedition Act!Aiyo! Teachers warned not to support Opposition!Aiseh! Won't Najib declassify audit report on 1MDB?This is the goonshit we get from the GOONvernment. Read about it and decide if you want a kakistocracy run by goodshitters, sygoonphants, shenanigoons and kleptogoons.